Changes in Sediment Flux from Hanjiang River into the Sea and Its Influence on Adjacent Sea Areas over the Last 60 Years - WANG Yufei; LIU Xiujuan; WANG Yang; WANG Wanhu; WANG Hongbing; YI Jiaji (Renmin Zhujiang)
In order to study the changes in sediment flux from the Hanjiang River into the sea and its environmental effects over the last 60 years,this paper uses the Mann-Kendall method to test the runoff discharge and sediment flux measured by the Chao'an hydrological station from 1958 to 2019,analyzes the main driving factors affecting the changes of sediment flux,and investigates the impact of sediment flux changes on adjacent sea areas.The results show that there is no significant change in runoff discharge for the Hanjiang River.The sediment flux into the sea has significantly decreased since 1998,and it has dropped more sharply since 2001.The large hydropower stations (Qingxi and Mianhuatan hydropower stations) in the Hanjiang River Basin are the main factors that lead to the significant decrease in the sediment flux into the sea.Since the sediments into the sea decreases greatly at the end of the 1990s,adjacent sea areas near the Hanjiang estuary have witnessed a transformation from slight sedimentation during 1971—2010 to slight erosion during 2010—2016 and a change of the delta shoreline from progradation (2.40~5.38 m/a) during 1830s—1964 to relative stability in 1980s.These findings indicate that the remarkable decrease in sediments from the Hanjiang River into the sea has greatly affected adjacent sea areas near the estuary.